Estimation on efficient of distribute channel allocation schemes for cellular network - Do, Huu Tri (H. : ĐHQGHN, 2017)
The efficient management and sharing of the spectrum among the users is an important issue, frequency channels have to be reused as much as possible in order to support the many thousands of simultaneous call in any typical of mobile system. In cellular architecture, cell is serviced by a base station located at its center. A number of cells are linked to a mobile switching center which also acts as a gateway of ihe cellular network to the existing wired networks liked PSTN, ISDN or LAN-WAN based networks. A base station communicates with the mobile station through wireless links, and with the MSC’s through wire-line links. This paper deals with some estimations on efficient of disừibute channel allocation scheme for cellular networks and then LBSB scheme is selected to improve it’s efficient, that is, the first, channel boưowing is not only neighbours but in compact pattern and the second, when a cell become hot, it repeat to borrow channel until reaching average degree of coldness of networks, that mean X=C.(dc^^^-dc).